POLA KONSUMSI PANGAN, KEBIASAAN MAKAN, DAN DENSITAS GIZI PADA MASYARAKAT KASEPUHAN CIPTAGELAR JAWA BARAT - Linda Dwi Jayati; Siti Madanijah; Ali Khomsan (Persagi, 2014)
ABSTRACTThe purpose of this study was to determine food consumption patterns, eating habits, and its effect on the density of nutrient intake in Kasepuhan Ciptagelar a traditional village community in West Java. Cross–sectional design was implied for this study. A total of 65 eligible households participated in the study. Household’s food consumption data which were used to calculate nutrient density score and density of nutrient intake were collected using 24-hour recall. Nutrient density scores were calculated by using Nutrient Rich Food Index 9.3 to compare nutrient intake of food with Daily Value based on FAO standards. Stepwise linear regression analysis showed that socio-economic factors most affecting iron density was age of husband. Meanwhile, food habits factor significantly affecting protein density was meal frequency. Food preference significantly affected on calcium density. Other socio-economic factors including family size, household income, and the amount of rice in rice barn; and socio-cultural factors of food taboos have no significant effect on density of nutrient intake. Nutrient intake from more variety foods should be increased to fulfill nutrient adequacy of individuals, especially girl adolescent and pregnant mothers who observed food taboos in this community.Keywords: density of nutrient intake, nutrient density, traditional communityABSTRAKPenelitian ini bertujuan menganalisis pola konsumsi pangan dan kebiasaan makan serta pengaruhnya terhadap densitas asupan zat gizi pada masyarakat Kasepuhan Ciptagelar di Jawa Barat. Desain penelitian ini adalah cross-sectional dengan total subjek sebanyak 65 rumah tangga. Skor densitas zat gizi pangan dihitung menggunakan metode Nutrient Rich Food Index 9.3. Analisis menggunakan regresi linear menunjukkan bahwa variabel umur suami berpengaruh terhadap densitas asupan zat besi rumah tangga. Salah satu variabel kebiasaan makan yaitu frekuensi makan rumah tangga berpengaruh signifikan terhadap densitas asupan protein rumah tangga, sedangkan preferensi pangan sayur-sayuran berpengaruh signifikan terhadap densitas asupan kalsium rumah tangga. Aspek sosial ekonomi rumah tangga lainnya meliputi besar keluarga, pendapatan perkapita, dan jumlah ketersediaan padi di dalam lumbung padi; serta salah satu aspek sosio-budaya pangan meliputi tabu makanan tidak berpengaruh terhadap densitas asupan zat gizi rumah tangga. Asupan zat gizi dari pangan lain sebaiknya lebih ditingkatkan untuk memenuhi kecukupan zat gizi individu, khususnya individu yang mempraktikkan tabu makanan pada masyarakat tersebut. [Penel Gizi Makan 2014, 37(1): 33-42]Kata kunci: densitas asupan zat gizi, densitas zat gizi pangan, masyarakat tradisional